(untitled) (Comprehensive Journal of Science, 2025)
Dentistry has undergone a significant transformation thanks to digital technologies, including 3D imaging, CAD/CAM systems, and 3D printing. While these tools enhance accuracy, efficiency, and the patient experience, they also pose challenges, such as high costs and psychological stress for practitioners. Despite the benefits of digitalization, barriers to adoption include expensive equipment and software, ongoing training requirements, data security issues, and psychological pressures on dental teams. This study aimed to collect and analyze clinical trials on digital applications in prosthetic diagnostics and treatment planning by examining their clinical relevance and future potential. It reviews the current status, advantages, limitations, and obstacles of using digital technologies in dental practice. A comprehensive search was performed across multiple electronic databases, including PubMed, Google Scholar, Scopus, and Web of Science. Keywords included “Digital workflow,” “Dental Imaging,” “CAD-CAM,” “Digital Dentistry,” “3D Printing,” “Intraoral Scanner,” “Artificial Intelligence (AI),” “Teledentistry,” and “3D Dentistry.” Articles published from 2017 onward, focusing on peer-reviewed journals and reviews with detailed insights into digital dentistry, were selected. Accuracy is improved by intraoral scanners, which reduce errors by up to 30% compared to traditional impressions. CAD/CAM systems can achieve up to 95% accuracy in crown fabrication. Digital design ensures consistent results and better reproducibility. Seventy percent of dentists report needing extensive training. In conclusion, digital technologies have transformed dentistry by increasing accuracy and reproducibility. However, widespread adoption depends on overcoming financial barriers. Enhancing training programs and providing psychological support for dental teams are essential. Additionally, AI is expected to play a larger role in diagnosis, and more research is needed to evaluate its impact on reducing treatment times. Long-term cost-benefit analyses of digitalization are also important. Furthermore, developing user-friendly digital tools to reduce practitioner stress remains a key priority.